Protecting older people living in care homes from COVID-19: a protocol for a mixed-methods study to understand the challenges and solutions to implementing social distancing and isolation. Issue 8 (4th August 2021) - Fitzpatrick, Joanne M; Rafferty, Anne Marie; Hussein, Shereen; Ezhova, Ivanka; Palmer, Sinead; Adams, Richard; Rees, Lindsay; Brearley, Sally; Sims, Sarah; Harris, Ruth
Abstract : Introduction: Older people living in residential and nursing care homes often have complex needs and are at high risk of poor health outcomes and mortality, especially if they contract COVID-19. Care homes use infection prevention and control measures such as social distancing and isolating residents to protect them from COVID-19. The care home sector has stated that implementing social distancing and isolation when caring for residents is a significant challenge. This paper presents the protocol of a mixed-methods study to explore and understand the real-life experiences of implementing social distancing and isolation of residents in care homes for older people from the perspective of residents, families/friends and staff working in and with care homes. The study aims to develop a toolkit of resources for health and care delivery now and for future outbreaks of infectious diseases. Methods and analysis: The study will be conducted in three phases. Phase 1 is a rapid review of evidence to collate knowledge on the mechanisms and measures used by care homes and long-term facilities to socially distance and isolate older people or control the spread of other infectious and contagious diseases. The review results will contribute to participant interviews in phase 2 and toolkit development in phase 3. Phase 2 will involve case studies with six care homes in England, involving the conduct of individual interviews with residents, families and friends, and staff, collection of care home policies and protocols related to social distancing and isolation for residents, and routinely collected care home data. A focus group with a purposive sample of external key informants will also be conducted. Phase 3, synthesising findings from phases 1 and 2, will inform the codesign of a toolkit of resources for residents, families/friends and care homes. Ethics and dissemination: The study has been approved by Coventry and Warwick Research Ethics Committee (20/WM/0318). To maximise impact, we will work closely with the Study Committees and the Patient and Public Involvement group to ensure the findings reach key stakeholders, including residents, families/friends, care homes, commissioners and organisations representing care home providers. We will disseminate the study outputs in peer-reviewed and professional journals, at professional conferences and via other knowledge transfer activities with the care home sector, and resident and carer organisations. The toolkit comprising evidence-informed guidance and resources and a mosaic film will be hosted on a project webpage. Registration details: This project is funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research Programme (Project reference NIHR132541). The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care. PROSPERO registration number: CRD42021226734.